Laura Rodriguez at OutSite : playing the "Game" of professional advancement (B) - Berger, Gail, (SAGE Business Cases., 2022)
This case provides an account of Laura Rodriguez's career trajectory and the obstacles she has faced-and still faces-as a female-identifying professional. Laura is portrayed as a hardworking, achievement-oriented individual who has excelled academically and professionally. But as she reaches the middle of her career, she is challenged in attaining her career objectives and does not receive a critical advancement opportunity given to her less-qualified male colleague. Part A of the case describes Laura's pre- and post-MBA career and the beginning of building her family. In Part A, she also learns she was not selected to participate in her firm's "Leadership Pathway" advancement program. Part B of the case describes Laura's leadership self-assessment and the development approaches she is contemplating.